INNOVATIVE TEACHING IN ACCOUNTING SUBJECTS: ANALYSIS OF THE FLIPPED CLASSROOM - Lubbe, E. (Social Sciences Research Society, 2018)
Accounting students often have a negative attitude towards the subject andstruggle to understand core concepts of accounting standards. A large percentageof accounting students do not prepare for class and homework is either not doneor neglected. Many factors contributed to students struggling to prepare for classand complete homework assignments. The flipped classroom approach has grownat a rapid pace and was perceived very successful in many subjects. Little researchhas been done on the effectiveness of this approach for accounting students.Videos was created whereby accounting theory was explained and questions withexamples were given and explained. All contact sessions were transformed into anactive learning environment. During contact sessions, students were provided withquestions. Guidance was given with regards to the interpretation of a practicalcase study. Students had to analyze questions before feedback was provided tothem. Contact sessions commenced with easy questions, and progressedto moredifficult questions.Research was conducted in order to determine whether a flipped classroommethod could improve the learning experience of accounting students at a highereducation institution. The study indicated that students watched the videos beforecontact sessions, they felt more positive about their performance in accountingand improved their time management. The majority of students that completed thesurvey preferred the flipped classroom method. It enables students to learn fromtheir own mistakes in class.